Successful laparoscopic cholecystectomy for acute cholecystitis with kyphoscoliosis by the devised placement of trocar ports: A case report - Takayama, Tomoyoshi (Int J Surg Case Rep, 2016)
INTRODUCTION: Kyphoscoliosis, which is a deformity of the spine caused by aging and osteoporosis, results in various surgical difficulties for laparoscopic cholecystectomy (LC) due to low-lying costal arches, such as a small abdominal working space, disturbance of the surgical view and decreased controllability of the surgical instrument. PRESENTATION OF CASE: We herein report the case of a 92-year old woman with severe kyphoscoliosis who was diagnosed with Grade II acute cholecystitis. Taking her general status into consideration, emergency percutaneous transhepatic gallbladder drainage (PTGBD) was initially performed. After PTGBD, the patient’s physical status and systemic inflammation markedly improved. She then underwent interval LC. The surgical view of the upper abdomen including the gallbladder was entirely interrupted by bilateral low-lying costal arches with adhesion to the greater omentum. To access the gallbladder without interruption by the low-lying costal arch, the first umbilical port was changed to a multi-port with surgical glove and an additional port was added in the left abdomen. Consequently, LC was safely accomplished with the creation of the critical view. DISCUSSION: A low-lying costal arch due to kyphoscoliosis can prevent surgeons from accessing the gallbladder. LC with the standard 4-port method could not be accomplished because of insufficient lifting of the low-lying costal arch. Devised placement of the ports is needed to access the gallbladder between bilateral low-lying costal arches. CONCLUSION: A transumbilical multi-port and left abdominal port may be effective for successful LC of acute cholecystitis with kyphoscoliosis.